Bio-inspired synthesis of mesoporous HfO2 nanoframes as reactors for piezotronic polymerization and Suzuki coupling reactions. Issue 12 (13th March 2019) - Wang, Haiqing; Sun, Dehui; Lu, Qichen; Wang, Fulei; Zhao, Lili; Zhang, Zengfu; Wang, Xun; Liu, Hong
Abstract : Mesoporous HfO2 nanoframes were elaborately fabricated, inspired by the flexible assembly principles in the biomolecules, and were demonstrated as nanoreactors for piezotronic polymerization and Suzuki coupling reactions. Abstract : Complex nanostructures with high compositional and structural tailorability are highly desired in order to meet the material needs in the rapid development of nanoscience and nanotechnology. Therefore, the synthetic technique is of essential importance but currently still suffers from many challenges. Herein, we elaborately explore and demonstrate the flexibility of the anisotropic metallo-organic compound (dihafnium dichloride, Cp2 HfCl2 ) for the fabrication of inorganic architectures by mimicking the assembly behaviors in biomolecules. The open and discrete architectures of mesoporous HfO2 nanoframes were constructed via the self-assembly of precursor with acetone as solvent and ammonia as the basic source, but without any addition of auxiliary organic molecules, like surfactants, DAN or peptides. In addition, the nanostructures (hollow spheres, solid spheres, yolk-shells, aggregations and defect-rich nanoparticles) of HfO2 assemblies can be well manipulated by simply modulating the synthesis parameters. The marked difference in the chemical bonds by the different ligands resulted in discrepant hydrolysis and then specific directional bonds for the diversity of the resultant HfO2 assemblies. Interestingly, the HfO2 nanoframe exhibits enhanced piezoelectricity, and can be used as a microelectrode reactor to trigger the pseudo-electrochemical aniline polymerization reaction by introducing ultrasonic excitation to renew the surface charges. Moreover, as compared with nanoparticle catalysts, the palladium (Pd) loaded nanoframe reactor exhibits obvious enhanced catalytic performance for classical Suzuki coupling, benefiting from the structural advantages of the HfO2 frame. Our findings here can be expected to offer new perspectives to find suitable materials by understanding the analogy between materials chemistry and biomolecule chemistry.